2021
DOI: 10.48550/arxiv.2107.10849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pristine Dwarf-Galaxy survey -- IV. Probing the outskirts of the dwarf galaxy Boötes I

Abstract: We present a new spectroscopic study of the dwarf galaxy Bootes I (Boo I) with data from the Anglo-Australian Telescope and its AAOmega spectrograph together with the Two Degree Field multi-object system. We observed 36 high-probability Boo I stars selected using Gaia Early Data Release 3 proper motions and photometric metallicities from the Pristine survey. Out of those, 29 are found to be Boo I's stars, resulting in an excellent success rate of 80% at finding new members. Our analysis uses a new pipeline dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Their candidate, and confirmed, member stars are RGB and HB stars redder than (g−i) 0,SDSS ∼ 0.2. As such, there is no overlap between the sample of Longeard et al (2021) and the candidate member stars identified in the present paper. Longeard et al (2021) found spectroscopically confirmed member stars out to ∼ 4 half-light radii from the center of Boo I and thirteen of the 29 total member stars identified in their study reside at projected distances further than two half-light radii from the center of Boo I.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Their candidate, and confirmed, member stars are RGB and HB stars redder than (g−i) 0,SDSS ∼ 0.2. As such, there is no overlap between the sample of Longeard et al (2021) and the candidate member stars identified in the present paper. Longeard et al (2021) found spectroscopically confirmed member stars out to ∼ 4 half-light radii from the center of Boo I and thirteen of the 29 total member stars identified in their study reside at projected distances further than two half-light radii from the center of Boo I.…”
Section: Discussionmentioning
confidence: 82%
“…After the analysis presented in this work was completed, the complementary investigation of Longeard et al (2021) was posted to the arXiv. These authors identified candidate Boo I member stars far from that galaxy's center using the metallicity-sensitive Pristine photometric filters (see e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations